2008
DOI: 10.1080/10428190802491698
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance ofFLT3gene abnormalities in Brazilian patients with infant leukemia

Abstract: Infant leukemia (IL) is characterised by the presence of MLL rearrangements and a poor outcome. FLT3 gene is consistently highly expressed in MLL+ patients. To correlate the clinical aspects of IL with FLT3 sequence alterations, we have analysed 159 children included in the Brazilian Collaborative Study Group of Infant Acute Leukemia. FLT3-D835 mutations and FLT3-ITD were detected by PCR-RFLP assay and standard PCR amplification, respectively. Mean age at diagnosis was 11.3 months. Overall, 7.5% (ITDs n=6 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
2
8
0
1
Order By: Relevance
“…on March 21, 2019. by guest www.bloodjournal.org From cells 14 and that secondary oncogenic hits may be required, making FLT3 activation a candidate. [15][16][17][18]21,39,42 The data presented here reveal that expression of the MLL-AF4 fusion oncogene together with FLT3 mutations does not confer either an in vitro proliferative or survival advantage to hESC-derived hemogenic precursors nor to CD45…”
Section: Flt3 Activation In Mll-af4-expressing Hescs 3871mentioning
confidence: 89%
See 2 more Smart Citations
“…on March 21, 2019. by guest www.bloodjournal.org From cells 14 and that secondary oncogenic hits may be required, making FLT3 activation a candidate. [15][16][17][18]21,39,42 The data presented here reveal that expression of the MLL-AF4 fusion oncogene together with FLT3 mutations does not confer either an in vitro proliferative or survival advantage to hESC-derived hemogenic precursors nor to CD45…”
Section: Flt3 Activation In Mll-af4-expressing Hescs 3871mentioning
confidence: 89%
“…This suggests that FLT3-activating mutations promote hESC hematopoietic specification rather than selective proliferation or survival of hESC-emerging hematopoietic derivatives. Several groups have reported the presence of FLT3-TKD mutations in MLL-rearranged ALLs, 15,16,39 whereas others have shown that FLT3 mutations in MLL-rearranged ALLs do not occur. 17,20,21,40,41 High expression of FLT3 is a hallmark step in the pathogenesis of MLL-AF41 ALL, 17 but it has not been resolved whether the constitutive activation of FLT3 in MLL-AF41 ALL is because of the presence of activating FLT3 mutations or simply the result of an increased expression of FLT3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups reported the presence of FLT3/tyrosine kinase domain (TKD) mutations in 3-20% of MLL-rearranged ALLs, 6,[12][13][14] whereas Stam et al 15,16 together with Bardini et al, 17,18 using high-resolution genomic analysis, showed that FLT3 mutations in MLL-rearranged ALLs do not occur. Despite this emerging controversy, FLT3 is consistently highly expressed in MLLrearranged ALL, and therefore it is not fully resolved whether the constitutive activation of FLT3 in MLL-rearranged ALL is due to the presence of activating FLT3 mutations, or simply due to a transcriptional increased expression of FLT3 in an attempt to provide blast cells with survival and proliferative advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that MLL-r B-ALL harbors FLT3 mutations in 3% to 21% of cases, [76][77][78] whereas others have shown that FLT3 mutations are not present in MLL-r B-ALL. 21,40,[79][80][81] Given that FLT3 is consistently highly expressed in MLL-r B-ALL, increased transcriptional expression of FLT3 rather than activating mutations could represent an important hallmark of MLL-r B-ALL.…”
Section: Etiology and Pathogenesis Of T(4;11)mentioning
confidence: 99%